2022
DOI: 10.1371/journal.pone.0266923
|View full text |Cite
|
Sign up to set email alerts
|

Role of serology tests in COVID-19 non-hospitalized patients: A cross-sectional study

Abstract: Introduction Severe acute respiratory syndrome coronavirus (SARS-CoV2) has imposed catastrophic impressions on the world. After all the focused researches conducted in the COVID-19 area, many features remain obscure. We have surveyed 1,363 outpatients with suspected COVID-19 in Tehran, Iran. The analysis emphasized on characteristics of patients with positive PCR or serology of SARS-CoV-2. Methods The nasopharyngeal swabs were tested for SARS-CoV2 PCR. Serum specimens were tested for SARS-CoV2 IgG and IgM. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…In one of the cross-sectional studies done in Iran, the study suggested that the patients who were IgG and IgM positive had more severe symptoms compared to patients who had negative serology. (14) If we see the relationship between the COVID-19 serology and complications, not many studies had been done in the past. This study had shown that patients who had higher COVID-19 IgG levels at three weeks had more severe ARDS and oxygen requirements compared to other patients.…”
Section: Discussionmentioning
confidence: 99%
“…In one of the cross-sectional studies done in Iran, the study suggested that the patients who were IgG and IgM positive had more severe symptoms compared to patients who had negative serology. (14) If we see the relationship between the COVID-19 serology and complications, not many studies had been done in the past. This study had shown that patients who had higher COVID-19 IgG levels at three weeks had more severe ARDS and oxygen requirements compared to other patients.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to PCR tests which are used to identify ongoing infection with SARS-CoV-2, serology tests are employed to provide information about vaccination efficiency, previous exposure, and severity of disease [ 6 ]. The Centers for Disease Control and Prevention (CDC) are utilizing these antibody tests as a means of surveillance to investigate how the virus is spreading throughout populations in the United States, and to learn more about the epidemiology of COVID-19 [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Asemptomatik veya hafif belirtilerle seyreden enfeksiyon durumunda viral yaygınlığın anlaşılmasında yararlıdır. Popülasyonda SARS-CoV-2 virüsüne karşı antikorların değerlendirilmesi, mevcut hastalarda ve iyileşmiş olgularda hastalık yayılımının anlaşılmasına yardımcı olur (16) . (17) .…”
Section: Introductionunclassified